Approximation of certain classes of differentiable functions by generalized splines - Polyakov, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We find the exnet value of the best (α, β)-approximation by generalized Chebyshev splines for a class of functions differentiable with weight on [−1, 1].